Pengaruh Komite Audit, Audit Eksternal, Profitabilitas Dan Ukuran Perusahaan Terhadap Manajemen Laba Pada Perusahaan Properti And Real Estate Yang Terdaftar Di BEI Tahun 2017-2019 - Yasmin Yasmin; Hartati Wau; Nabila Tatcher; Nintha Katharina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
In this investigation, it is relied upon to test the influence of the audit committee as measured by the size of the number of committee members, and external audit is measured by whether the company uses the big four watchdog or not, then profitability is measured using the ROA (Return On Assets) ratio, and the size of the company in measure using total assets which are logarithmic to Ln. Then on earnings management using the Jones Model method which is Discrectionary accruals. This study uses a quantitative strategy, and uses 54 populations or companies from sampling at www.idx.co.id about property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019 and the number of observations for 3 years is 162 samples. , using the method used in the study, namely purposive sampling which was analyzed using multiple linear regression and made the sample reduced to 123 samples, for the results of the study showed that (1) the audit committee (X1) had no impact and was not significant on earnings management ( 2) External audit (X2) has no impact and is not significant on earnings management (3) Profitability (X3) has no adverse and insignificant consequences on earnings management (4) Company size (X4) has no effect, which means it has a negative effect and does not means to earnings management. The audit committee, external audit, profitability, and firm size also have no adverse and insignificant consequences for earnings management. Keywords : Number of Committee Members, Big Four, Return On Assets, Ln.